Global variability in leaf respiration in relation to climate, plant functional types and leaf traits. Issue 2 (8th January 2015) - Atkin, Owen K.; Bloomfield, Keith J.; Reich, Peter B.; Tjoelker, Mark G.; Asner, Gregory P.; Bonal, Damien; Bönisch, Gerhard; Bradford, Matt G.; Cernusak, Lucas A.; Cosio, Eric G.; Creek, Danielle; Crous, Kristine Y.; et al.
Summary: Leaf dark respiration ( R dark ) is an important yet poorly quantified component of the global carbon cycle. Given this, we analyzed a new global database of R dark and associated leaf traits. Data for 899 species were compiled from 100 sites (from the Arctic to the tropics). Several woody and nonwoody plant functional types (PFTs) were represented. Mixed‐effects models were used to disentangle sources of variation in R dark . Area‐based R dark at the prevailing average daily growth temperature ( T ) of each site increased only twofold from the Arctic to the tropics, despite a 20°C increase in growing T (8–28°C). By contrast, R dark at a standard T (25°C, R dark 25 ) was threefold higher in the Arctic than in the tropics, and twofold higher at arid than at mesic sites. Species and PFTs at cold sites exhibited higher R dark 25 at a given photosynthetic capacity ( V cmax 25 ) or leaf nitrogen concentration ([N]) than species at warmer sites. R dark 25 values at any given V cmax 25 or [N] were higher in herbs than in woody plants. The results highlight variation in R dark among species and across global gradients in T and aridity. In addition to their ecological significance, the results provide a framework for improving representation of R dark in terrestrial biosphere models (TBMs) and associated land‐surface components of Earth system models (ESMs). Abstract : See also the Commentary by Wullschleger et al